Otherwise Known as Sheila the Great - Blume, Judy (New York, 2002)
A summer in Tarrytown, New York, is a lot of fun for ten-year-old Sheila even though her friends make her face up to some self-truths she doesn't want to admit.
"A Yearling book."
Keywords: Conduct of life; Fiction; Friendship; Fiction; Self-acceptance; Fiction